Toxicity and Immunogenicity of a Tardigrade Cytosolic Abundant Heat Soluble Protein in Mice - Esterly, Harrison J.; Crilly, Candice J.; Piszkiewicz, Samantha; Shovlin, Dane J.; Pielak, Gary J.; Christian, Brooke E. (Frontiers in Pharmacology, 2020)
Tardigrades are microscopic animals well-known for their stress tolerance, including the ability to survive desiccation. This survival requires cytosolic abundant heat soluble (CAHS) proteins. CAHS D protects enzymes from desiccation-and lyophilization-induced inactivation in vitro and has the potential to stabilize protein-based therapeutics, including vaccines. Here, we investigate whether purified recombinant CAHS D causes hemolysis or a toxic or immunogenic response following intraperitoneal injection in mice. CAHS D did not cause hemolysis, and all mice survived the 28-day monitoring period. The mice gained weight normally and developed dose-dependent anti-CAHS D antibodies but did not show upregulation of the inflammatory cytokines interlukin-6 and tumor necrosis factor alpha. In summary, CAHS D is not toxic and does not promote an inflammatory immune response in mice under the conditions used here, suggesting the reasonability of further study for use as stabilizers of protein-based therapeutics.